BLENDED LEARNING, MODEL PEMBELAJARAN ABAD ke-21 DI PERGURUAN TINGGI - Milya Sari (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2014)
The rapid progress of information and communication technology in the 21th centuryforced teachers who teach students at any levels of education to change their behaviour and mind-set, even the the commitee that supported them to achieve their teaching objective. A good approach is that a way in which one could integrate technology and education, that was through Blended Learning Model (BLM). This model combined the usual teaching classroom and teaching online. The strength of this model was that this could increase the interaction among the students whenever and wherever.Kata kunci: Model Blended Learning, TIK, pembelajaran abad 21